Contesting femicide: feminism and the power of law revisited - Howe, Adrian; Alaattinoğlu, Daniela (A GlassHouse book, 2019)
Preface / Carol Smart -- Provocation by "sexual infidelity" - diminishing returns? / Adrian Howe -- Feminist dilemmas with law reform : Victoria, Australia / Danielle Tyson and Bronwyn Naylor -- Criminalising femicide in latin american countries : legal power working for women? / Patsili Toledo -- "Being wrought, perplexed in the extreme" : Othello and his syndrome / Adrian Howe -- Fighting femicide in Turkey : feminist legal challenges / Daniela Alaattinoglu and Cemre Baytok -- The Canadian femicide observatory for justice and accountability / Myrna Dawson -- Judicial discourse versus domestic violence death review : an Australian case study / Anna Butler and Emma Buxton-Namisnyk -- Italian legal feminism : engaging with the power of law / Ilaria Boiano -- Legal education : challenging the Finnish criminal law syllabus / Daniela Alaattinoglu and Johanna Niemi -- Finland on trial / Marjo Rantala -- Epilogue